Profile of syphilis in pregnancy at the Dermatovenereology Clinic, Bali Mandara General Hospital (2020–2024) - Febri Evalina Trisnawati; Luh Putu Dina Wahyuni (Bali Dermatology Venereology and Aesthetic Journal, 2025)
Introduction: Syphilis is a chronic and systemic sexually transmitted infection (STI) caused by Treponema pallidum. There are four stages of syphilis based on clinical manifestations: primary, secondary, latent, and tertiary. This study aimed to obtain data on pregnant women diagnosed with syphilis and their characteristics at the Dermatovenereology Clinic of Bali Mandara General Hospital, Denpasar, from January 2020 to December 2024. Methods: This research utilized a retrospective descriptive design by collecting secondary data from the medical records of patients who visited the Dermatovenereology Clinic of Bali Mandara General Hospital, Denpasar, during the period of January 2020 to December 2024. Results: A total of 23 cases of syphilis in pregnancy were recorded between January 2020 and December 2024, distributed as follows: 2 cases in 2020 (8%), 1 case in 2021 (5%), 14 cases in 2023 (61%), and 6 cases in 2024 (26%). The majority of cases occurred in women aged 26–35 years (52%). Most patients (15 individuals) were in their third trimester of pregnancy, and late latent syphilis was the most common stage found (87%). Conclusion: Between 2020 and 2024, there were 23 cases of syphilis in pregnancy at Bali Mandara General Hospital, with most cases classified as late latent syphilis diagnosed in the third trimester.